Automated solid-phase extraction method for the determination of piperaquine in capillary blood applied onto sampling paper by liquid chromatography. - Malm, M; Lindegårdh, N; Bergqvist, Y (2004)
A bioanalytical method for the determination of piperaquine in 100 microL blood applied onto sampling paper, by solid-phase extraction and liquid chromatography, has been developed and validated. Blood spots were cut into small pieces prior to addition of 0.3M perchloric acid, acetonitrile and phosphate buffer containing an internal standard. The liquid phase was loaded onto a mixed phase cation-exchange (MPC) solid-phase extraction column. Piperaquine and the internal standard were analysed by liquid chromatography and separated on a Chromolith Performance (100 mm x 4.6 mm) column with acetonitrile:phosphate buffer pH 2.5, I = 0.1 (8:92, v/v) at the flow of 3.5 mL/min. The UV detection was performed at 345 nm. The intra-assay precision was 12.0% at 0.150 microM, 7.3% at 1.25 microM and 7.3% at 2.25 microM. The inter-assay precision was 1.8% at 0.150 microM, 5.2% at 1.25 microM and 2.8% at 2.25 microM. The lower limit of quantification (LLOQ) was determined to 0.050 microM where the precision was 14.7%.